Association of Biomarker Discrepancy and Treatment Decision, Disease Outcome in Recurrent/Metastatic Breast Cancer Patients - Lu, Yujie; Tong, Yiwei; Chen, Xiaosong; Shen, Kunwei (Frontiers in Oncology, 2021)
Background: Biomarker discrepancy between primary and recurrent/metastatic breast cancer is well known, however its impact on prognosis and treatment after relapse is still unclear. Current study aims to evaluate biomarkers discrepancy between primary and recurrent/metastatic lesions as well as to investigate its association with following treatment pattern and disease outcome. Patients and methods: We retrospectively included consecutive breast cancer patients undergoing surgery in our center from Jan. 2009 to Dec. 2016 and reported disease recurrence. Patients with re-biopsy and paired biomarkers statuses on primary and recurrent/metastatic lesions were further analyzed. Kappa test was used to analyze the concordance rate of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor-2 (HER2) status. Post-recurrence survival (PRS) was compared between subgroups by Kaplan-Meier curve. Cox regression model was applied to identify impact factors for PRS. Results: A total of 156 patients were finally included, of whom 70 and 86 had loco-regional and distant recurrence, respectively. Concordance rates of ER, PR and HER2 were 83.3%, 66.7%, and 97.1%, respectively, which was similarly distributed among different recurrent sites (all P > 0.05). Primary ER-positivity (vs ER-negativity, P = 0.014) and loco-regional recurrence (vs distant metastasis, P = 0.001) were independently associated with superior PRS, while patients with visceral metastasis (P < 0.001) had the worst disease outcome. Hormone receptor/HER2 status discrepancy was observed in 28 patients. Fifteen of them changed systemic treatment based on biomarker statuses of recurrent lesion, however, their PRS was not improved compared to those 13 patients who continued the same treatment according to primary biomarkers statuses (P = 0.298). Conclusion: Biomarker discrepancy was observed between primary and recurrent/metastatic breast cancer lesions and had certain influence on treatment strategies after relapse. However, its impact on disease outcome wasn’t established in the current study, which deserves further evaluation.